DIVERSIFIKASI PENGOLAHAN HERBAL DALAM RANGKA MENGEMBANGKAN DIMENSI PRODUK TOGA DI DESA SIWALANPANJI - Moch. Dicky Riza; Endah Alamsari Andayani; Afifatus Karunia; Aulia Anaya Putri; Dwi Putri Eka Ratna Avifah; Izah Nurfitriyah; Novi Ardiani; Putri Nova Rizqi Febriyanti (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2022)
KKN is a learning activity in the field carried out by students as a form of community service. The thematic of KKN Mandiri at STKIP PGRI Sidoarjo is "Creative Economy" held in Siwalanpanji Village which has a developing UMKM work program. “UMKM” stands for Micro, Small, Medium Enterprises. The focus of the activity was making herbal bag products and product packaging logo designs as a form of diversification of herbal processing in order to develop TOGA products in Siwalanpanji Village. This activity goes through several stages, including: planning, preparation, processing of herbal ingredients, product packaging design, packaging, and the product socialization stage. This activity produced sour turmeric herbal products and white turmeric-curcuma herbal bag products packaged in tea bags and white boxes using the product logo label "Kunjare" as the TOGA processed product brand owned by the PKK driving Team in Siwalanpanji Village. Keywords : Diversification, TOGA Product, Herbal Infusion, Siwalanpanji Village